An omni-directional multirotor vehicle. (November 2018) - Brescianini, Dario; D'Andrea, Raffaello
Abstract: In this paper we present the design, modelling and control of an omni-directional multirotor vehicle, i.e. a fully-actuated vehicle that can hover at any attitude and accelerate in any direction. Based on a static force and torque analysis for generic rotor configurations, an octorotor configuration is derived that maximizes the vehicle's agility while rendering its characteristics almost rotationally invariant. A prototype vehicle with the derived rotor configuration is built using reversible fixed-pitch rotors that can generate positive and negative thrust, enabling the vehicle to independently control its thrust and torque in all three dimensions. A control scheme that allows for simultaneously tracking a desired position and attitude trajectory is introduced. Experimental results demonstrate the feasibility of the vehicle design and control strategy.